(untitled) (Fiep Bulletin - online, 2014)
Adventure and Risk are outstanding topics in an ever-growing universe of Eco-tourism and sports-oriented activities. Stemming from rational, sensitive and symbolic knowledge, and presupposing the existence of a discourse based on the sacredness features of such activities, this investigation was carried out in the field of Social Imaginary knowledge, involving people engaged in the pursuit of Eco-tourism sports, such as leisure in the mountains. This qualitative research had two objectives: (a) to investigate adventure and risk expressed in the discourse made by nature sports adepts, and in Internet sites related to the publicity of adventure-type tourism; and (b) to evidence symbolic and mythical elements that emerge from these discourse pieces. Based on Durand and Bachelard and by Eliade and Caillois, the adopted methodological strategy was the path taken to reach sacredness. Caillois and Duvignaud have contributed with the notion of playfulness and game. Schiller provided the aesthetic fundaments. A series of 11 semi-structured interviews was carried out with mountaineers and representatives of climbing, river canoeing and trekking activities. We have applied Eny Orlandi’s discourse analysis. The analysis of sites and discourses has indicated that climbing a mountain or canoeing down a river are not mechanical acts. They impose rituals that approach people to divinity, rendering their lives sacred. The more they win, the closer they get to religiosity, living a perfect personal adventure for the sake of freedom and transcendence. In Nature they reencounter their nature-being, the divine essence that exists in themselves, inwardly. Within myths that render meaning to the lives of those Eco-tourism sports adepts, we can identify Prometheus, Ulysses, Icarus, Dionysius, Hercules, but we thought the infusing allegory to be adopted was the Apollo myth (The Oracle God), whose symbolism is spirituality. Apollo’s advice can be a guide into the adventure of assigning sense to the lives of these sport people — "Know thyself". Sports in Nature is governed by double-faced Janus, the God who features both archaic and modern traits (lord of passages).